PENGARUH PEMUPUKAN NITROGEN, FOSFOR DAN KALIUM PADA PERTUMBUHAN TUNAS KANGKUNG (IPOMOEA AQUATICA FORST.) - SAEFUDIN SAEFUDIN; R. SANTOSA (Research Center for Biology-Indonesian Institute of Sciences, 1986)
SAEFUDIN & R. SANTOSA.1986.The effect of nitrogen, phosphorous and potassium fertilizers on the growth of Ipomoea aquatica Forst. Berita Biologi 3 (5): 214-218.Experiments to study the effect of nitrogen, phosphorous and potassium fertilizers on the growth of Ipomoea aquatica, a leafy vegetable, were carried out on four sites, i.e. in the villages of Teluk, Karangklesem, Purwokerto Kulon and Sumampir of the district of Banyumas respectively. The rates of application used were 0, 125, 250 and 375 kg of urea, triple superphosphate or potassium chloride per ha. The nitrogen fertilizer increased significantly the growth of Ipomoea aquatica with optimum rate 250 kg of urea per ha. Potassium chloride increased slightly the stem elongation, but not the vegetable yield, while the phosphorous fertilizer did not show any significant effect.Among sites, the highest yield was obtained from the plot in the village of Teluk, followed by Karangklesem, Purwokerto Kulon and Sumampir in decreasing order.